The association of the seroprevalence and associated risk factors of toxoplasmosis in Cebu, Philippines - Jayma, Erika Ashley Meg G. (Animo Repository, 2023)
Toxoplasmosis is a parasitic infection caused by the intracellular parasite Toxoplasma gondii. It is capable of harming not only humans but also other animals that they depend on for the continuation of their life cycle. This research aims to determine if there is an association between risk factors and seroprevalence of T. gondii in Cebu. The Chi-square test and the odds ratio formula were used in this study to assess the risk factors for toxoplasmosis in Cebu, Philippines. In humans, four risk factors were identified that show statistically significant association, namely their residence area (p = 0.0011, OR = 1.73 for suburban vs. rural; p = 0.0002, OR = 2.50 for suburban vs. urban), preference for pet cats (p = 0.0205; OR=1.48), their frequency of contact with cats (p =T. gondii thrives in soil, food, and cats, which serve as intermediate hosts, an area's hygienic measures are important in maintaining low seroprevalence levels of toxoplasmosis. Preventive measures such as paved roads, safety precautions for street food vendors, and reducing the population of stray cats to a minimum and caring for their well-being can decrease seroprevalence levels.